Effect of Hypoxia on Diet of Atlantic Bumpers in the Northern Gulf of Mexico. Issue 4 (7th June 2018) - Glaspie, Cassandra N.; Clouse, Melissa A.; Adamack, Aaron T.; Cha, YoonKyung; Ludsin, Stuart A.; Mason, Doran M.; Roman, Michael R.; Stow, Craig A.; Brandt, Stephen B.
Abstract: Cultural eutrophication is a global problem that often leads to hypoxic conditions in coastal systems. Although improving, our understanding of the impacts of hypoxia on trophic interactions in pelagic and benthopelagic food webs is limited. Toward this end, we evaluated diet composition of and mass‐specific consumption by the Atlantic Bumper Chloroscombrus chrysurus, a numerically dominant planktivorous fish in the northern Gulf of Mexico, relative to dissolved oxygen concentration and fish size. Atlantic Bumper CPUE was similar in hypoxic and normoxic areas. Mean mass‐specific consumption by small Atlantic Bumpers in hypoxic areas was greater than that of both small and large individuals in normoxic areas. The most commonly ingested prey type for both large and small Atlantic Bumpers was shrimp larvae. Large quantities of fish larvae were consumed by adult Atlantic Bumpers in hypoxic regions. These findings demonstrate that hypoxic conditions can alter feeding of dominant fishes in the northern Gulf of Mexico, which may influence energy flow in the region.